A labor market approach to the crisis of health care professionals in Africa - Mabel Andalón; Gary Fields (Institute for the Study of Labor (IZA), 2011)
This paper adopts a labor market economics perspective to understanding the crisis of health care professionals in Africa. Five challenges resulting from this crisis are identified: a production challenge, an underutilization challenge, a distributional challenge, a performance challenge, and a financing challenge. Differences between the labor market approach and others used in the health field are noted. We conclude that more empirical data, a full labor market analysis, and the use of social benefit-cost criteria are all needed before policy recommendations to address any of these challenges can be confidently offered.
urn:nbn:de:101:1-201104113568
Keywords: I11; J01; J08; 330; labor market; health care; Africa; Gesundheitsberufe; Arbeitsmarkt; Gesundheitsversorgung; Gesundheitsfinanzierung; Afrika